Pengaruh E–Commerce di Era Digital Terhadap Pola Konsumsi Mahasiswa Universitas Pancasakti Tegal - Ramadan, Septyan Bayu; Fr, Dewi Apriani; Basukiyatno; Nafiati, Dewi Amaliah (Jurnal Pendidikan Ekonomi Undiksha, 2025)
This study aims to analyze the influence of e-commerce in the digital era on the consumption patterns of Pancasakti Tegal University students. The development of internet technology has given birth to e-commerce that changes the way people shop, providing easy access without restrictions on distance, time, and energy to meet daily needs. The research method uses a quantitative approach with survey techniques. Data collection was carried out through questionnaires, observations, interviews, and documentation. The research population is all active students of Pancasakti Tegal University totaling 6,298 students based on data from the Bureau of Academic and Student Administration (BAAK). The sample was determined using the Slovin formula with a result of 98.40 which was rounded up to 100 respondents. Data analysis techniques include validity, reliability, normality, hypothesis, and t-test. The results of the study show that there is a positive and significant influence of e-commerce on the consumption patterns of Pancasakti University students of Tegal. This proves that online shopping platforms in the digital era have significantly changed student consumption behavior, both in terms of frequency, type of product, and way of shopping. These findings indicate that the digitalization of commerce has become an integral part of students' lives and influences their consumption decisions substantially.